MicroRNAs em abelhas: busca e caracterização de proteínas da via, miRNAs e seus alvos - Araújo, Carlos Bruno de (2022)
Bees are millennial insects that had their emergence long before humans, something like hundreds of millions of years ago. Their domestication is as old as being worshiped as a symbol of wealth work and perseverance in ancient Egypt. Belonging to the phylum Arthropoda, class Insecta, and order Hymenoptera, it is believed that bees are originally from a group of wasps that, for millions of years of evolution, had dietary modifications, leftover a diet based on insects and mites, and starting to obtain nutrients by nectar and pollen from flowers. There are about 20 thousand species around the world, with about 1678 described in Brazil, but it is expected that the real number is about 2500 species, attributing to Brazil as one of the biggest diversities on the planet. Bees have an amazing and complex habits and behaviors, mainly about de Eusociability, lifestyle, where they can be characterized as social bees, solitary bees and parasite. The bee’s lifestyle is one of the most characteristics that has made this animal of the subject of many researchers trying to elucidate the factors of influence in this aspect. Two molecules have been the central point in this study, Vitellogenin and Juvenile Hormone, that is because these molecules already showed essential importance in the life cycle of bees and because they influence bees’ differentiation, even during the layoff of eggs. Juvenile hormone is responsible for the embryonic development in this insect, been present in the maturation of larval, pulpal stages, and metamorphosis, and yet in a variety of others biological processes that impact the reproduction and behavior in bees. Vitellogenin play a role in larval differentiation through the caste system used in hive organization. It is an essential protein involved in reproduction, being the central nourishment to embryo, it is noticed that their availability is capable of differentiating the egg into a queen or worker. This study aims to search and characterizes a third molecule able to interact in the biological function with both of them. microRNAs are small non-coding RNAs, and they control and regulatecontrol and regulate gene expression in post-transcriptional ways. This analysis will use bioinformatic tools to search and characterize proteins involved in the miRNA pathway and miRNAs and their targets in the genome of eight different species of bees, as both social and solitary ones, focusing on their action in Vitellogenin and Juvenile Hormone modulation.